مخدوم محمد ہاشم ٹھٹوی : قرآنیات سے متعلق تصانیف کا تعارفی مطالعہ: Makhdoom Muhammad Hāshim Thattvī: An Introductory Study of Writings on Qur’ānic Sciences (Al-Qamar, 2021)
Makhdoom Muhammad Hāshim Thattvī (1692- 1761) was one of the eminent Islamic scholars, authors, jurists, interpreters of Quran and Ḥadīth from Sindh. His expertise in various branches of Islamic knowledge is matchless. He made a great contribution toward understanding and interpreting Quran, Ḥadīth and Fiqh. He wrote approximately 350 books and booklets on various topics of Islamic sciences. His books are filled with precious Knowledge of Quran, ḤadIth and Fiqh. He has also produced great work in the field of Qur’ānic studies and wrote tafsīr in Arabic and Sindhi languages which is known as al-Tafsīr al-Hāshmī and Tafsīr-i-Hāshmī. This article presents an introductory study of his works on Qur’ānic sciences. It explores that Thattvī, has provided precious literal and exegetical meanings of Qur’ānic words. He interpreted the Quran with the help of Quran, ḥadīth and sayings of Prophet's companions.
Keywords: Makhdoom Muhammad Hāshim Thathvī; works; Arabic; Sindhi; Tafsīr